Experimental periodontal disease treatment by subgingival irrigation with tetracycline hydrochloride in rats - Leandro Araújo Fernandes; Thiago Marchi Martins; Juliano Milanezi De Almeida; Maria José Hitomi Nagata; Leticia Helena Theodoro; Valdir Gouveia Garcia; Alvaro Francisco Bosco (University of São Paulo, 2010)
OBJECTIVE: The aim of this study was to compare subgingival irrigation with tetracycline hydrochloride (TTC-HCL) as adjunctive treatment to scaling and root planning (SRP) on induced periodontitis in rats. MATERIAL AND METHODS: In 60 rats, periodontal disease was ligature-induced at the mandibular left first molar. After 7 days, the ligature was removed and all animals were submitted to SRP, and divided into 2 groups according to the following treatment: C (n=30) - subgingival irrigation with 1 mL of saline; T (n=30) - subgingival irrigation with 1 mL of TTC-HCL (50 mg/mL). Ten animals in each group were euthanized at 7, 15 and 30 days posttreatment. The histometric values were statistically analyzed (p<0.05). RESULTS: In the histometric analysis, at 7, 15 and 30 days, Group T (0.72±0.05 mm², 0.57±0.14 mm², 0.62±0.07 mm²), showed less bone loss (p<0.05) than Group C (1.35±0.25 mm²; 1.40±0.31 mm²; 1.29±0.27 mm²), respectively. CONCLUSIONS: Subgingival irrigation with TTC-HCL was an effective adjunctive treatment for periodontal disease induced in rats.